The Importance of Dead Seagrass (Posidonia oceanica) Matte as a Biogeochemical Sink - Apostolaki, Eugenia T.; Caviglia, Laura; Santinelli, Veronica; Cundy, Andrew B.; Tramati, Cecilia D.; Mazzola, Antonio; Vizzini, Salvatrice (Frontiers in Marine Science, 2022)
We assessed the potential of dead seagrass Posidonia oceanica matte to act as a biogeochemical sink and provide a coherent archive of environmental change in a degraded area of the Mediterranean Sea (Augusta Bay, Italy). Change in sediment properties (dry bulk density, grain size), concentration of elements (Corg, Cinorg, N, Hg) and stable isotope ratios (δ13C, δ 15N) with sediment depth were measured in dead P. oceanica matte and unvegetated (bare) sediments in the polluted area, and an adjacent P. oceanica meadow. Principal Component Analysis (PCA) revealed a clear clustering by habitat, which explained 72% of variability in our samples and was driven mainly by the accumulation of N and Hg in finer sediments of the dead matte. Assessment of the temporal trends of Corg, N and Hg concentrations in the dead matte revealed changes in the accumulation of these elements over the last 120 years, with an increase following the onset of industrial activities 65 y BP (i.e., yr. 1950) that was sustained even after seagrass loss around 35 y BP. Despite a decrease in Hg concentrations in the early 1980s following the onset of pollution abatement, overall Hg levels were 2-fold higher in the local post-industrial period, with a Hg enrichment factor of 3.5 in the dead matte. Mean stocks of Corg, N and Hg in 25 cm thick sediment deposits (4.08 ± 2.10 kg Corg m-2, 0.14 ± 0.04 kg N m-2, 0.19 ± 0.04 g Hg m-2) and accumulation in the last 120 yr (35.3 ± 19.6 g Corg m-2 y-1, 1.2 ± 0.4 g N m-2 y-1, 0.0017 ± 0.0004 g Hg m-2 y-1) were higher in the dead matte than bare sediment or adjacent P. oceanica meadow. Our results indicate that dead P. oceanica matte maintained its potential as a biogeochemical sink and, like its living counterpart, dead matte can serve as an effective archive to allow for reconstructing environmental change in coastal areas of the Mediterranean where severe perturbations have led to P. oceanica loss. Appropriate management for contaminated areas should be prioritized to prevent release of pollutants and carbon from dead mattes.